2023
DOI: 10.3389/fimmu.2023.1067291
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and age-specific associations of childhood maltreatment with peripheral serum inflammatory cytokines in middle school students

Abstract: BackgroundThe impact of childhood maltreatment on multiple inflammatory cytokines among middle school students remains to be elucidated. This study aimed to examine the associations of different types of childhood maltreatment with peripheral serum inflammatory cytokines (interleukin-10, interleukin-1β, interleukin-6, interleukin-8, and tumor necrosis factor-α) in middle school students, and to explore the differences in these associations between boys and girls and between late (≥15 and<20 years) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Additionally, we found that significant differences in inflammatory factor levels between the control and MDD groups were not retained when ELS was adjusted. This is indicative of the potential role of ELS in inflammation and (45)(46)(47)(48). Thus, future studies are warranted to further explore the relationship between ELS and inflammation, especially in children and adolescents.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we found that significant differences in inflammatory factor levels between the control and MDD groups were not retained when ELS was adjusted. This is indicative of the potential role of ELS in inflammation and (45)(46)(47)(48). Thus, future studies are warranted to further explore the relationship between ELS and inflammation, especially in children and adolescents.…”
Section: Discussionmentioning
confidence: 94%
“…Despite various preventive efforts by the World Health Organization (WHO) and many nations—ranging from epidemiological studies and social awareness campaigns to changes in laws 3 —biological perspectives on early detection efforts remain limited. Several studies have explored potential biomarkers for the early detection of childhood maltreatment, including brain MRI 4 8 , epigenomic analyses 9 11 , and hormone and cytokine 12 14 measurements. However, these investigations are largely pilot studies, lacking established indicators and remaining in the early stages of exploring a wide range of possible biomarkers that reflect childhood maltreatment features.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) and many nations have made various preventive efforts for the early detection of child maltreatment through epidemiological studies, social awareness campaigns, and changes in laws [2], but limited effort from a biological perspective. Studies have attempted to nd biological characteristics that would contribute to the development of biomarkers for the early detection of maltreated children (CM), including brain MRI [3][4][5][6][7], epigenome [8][9][10], and hormone and cytokine [11][12][13] measurements. However, these remain largely pilot studies; there are no established indicators and are in the early stages of exploring a wide range of possible biomarkers that re ect CM.…”
Section: Introductionmentioning
confidence: 99%